Mortality After Paclitaxel-Coated Device Use in Patients With Chronic Limb-Threatening Ischemia: A Systematic Review and Meta-Analysis of Randomized Controlled Trials. (April 2020) - Dinh, Krystal; Gomes, Miguel Lemos; Thomas, Shannon D.; Paravastu, Sharath C.V.; Holden, Andrew; Schneider, Peter A.; Varcoe, Ramon L.
Purpose: To report the risk of all-cause mortality after treatment with paclitaxel-coated devices vs uncoated controls in patients with chronic limb-threatening ischemia (CLTI). Materials and Methods: A search of the PubMed, Embase, Cochrane, CINAHL, DARE, and PROSPERO databases was made on 5 November 2019 to identify randomized controlled trials (RCT) using intention-to-treat analysis to compare a paclitaxel-coated device to an uncoated device in PAD patients having clinical follow-up of at least 6 months. Half of the study population had to have CLTI or extractable data on the CLTI subgroup if <50%. The search identified 11 trials having 1450 patients randomized to a paclitaxel-coated device (n=866) or an uncoated control (n=584). There were 1367 (94.3%) patients with CLTI (range 10–429). The single endpoint was all-cause mortality, which was analyzed by pooling the mortality data in a DerSimonian and Laird random effects model. Summary statistics are expressed as relative risk ratios (RR) with a 95% confidence interval (CI). Results: The mean follow-up was 25.6 months (range 6–60); 10 of 11 studies reported a minimum 12-month follow-up. There were 161 (18.6%) deaths among 866 subjects in the paclitaxel device group and 116 deaths among 584 (19.9%) subjects in the non-coated control group (RR 0.93, 95% CI 0.78 to 1.12, p=0.45). Conclusion: There was no observed difference in short- to midterm mortality among a pooled patient population of predominately CLTI patients treated with paclitaxel-coated balloons or stents compared with uncoated controls.